How the landscape of publishing is changing biogeography - Michael N Dawson; Alycia L Stigall; Joaquín Hortal (Frontiers of Biogeography)
Open access, shifting publishing mores, predatory journals, reviewer over-burden are just a few of the factors reshaping modern scientific publishing. How are changes in the publishing environment influencing biogeography?  Over the past eight years, 63 different titles have been among the 25 journals publishing most “biogeography” articles in any given year; a small nucleus of journals has consistently published a large proportion of “biogeography” papers.  Yet, the journals enjoying the largest positive trends—e.g. increasing share of biogeography publications and increasing Impact Factor—are outside of the nucleus; they are emerging open access ‘mega-journals’ that offer simplified criteria for publication. From the fault lines appearing across the publishing landscape, we see opportunities emerging for Frontiers of Biogeography as a vigorous hybrid model that leverages the strengths of ‘old world’ and ‘new world’ approaches to disseminating scientific knowledge and nurtures mutual benefits.